Herpes zoster vaccine and the risk of stroke: a population-based cohort study using linked data from the Clinical Practice Research Datalink - Fawziah Marra; Kathryn Richardson; Helen I McDonald; Yoon Kong Loke; Helen Mary Parretti (BMJ Public Health)
Background Studies report herpes zoster associated with short-term stroke risk, but it is unclear whether herpes zoster vaccine reduces stroke risk.Methods We performed cohort studies using Clinical Practice Research Datalink Aurum linked to hospital admission, mortality and deprivation data. We included 678 110 adults aged 70–80 years receiving a live attenuated herpes zoster vaccination between 1 September 2013 and 31 December 2019. We conducted three comparisons to a historical unvaccinated cohort, an active comparator and a self-controlled case series (SCCS). The historical cohort comprised 678 110 matched unvaccinated adults between 2007 and 2012. The active comparator comprised 653 373 adults receiving an influenza vaccination between 2013 and 2019 meeting herpes zoster vaccine eligibility. Cox regression was used to estimate HRs for stroke in the subsequent 5 years adjusted for measured confounders, in the vaccinated compared with comparator cohorts. Secondary outcomes included stroke/transient ischaemic attack and myocardial infarction. The SCCS included incident strokes 12 months before or after herpes zoster vaccination to address healthy vaccinee bias.Results We recorded 16 281 and 30 430 incident strokes among vaccinated and unvaccinated historical patients, over a median of 2.7 and 5.0 years follow-up, respectively. The adjusted HR for stroke for herpes zoster vaccination compared with unvaccinated historical patients was 0.84 (95% CI 0.82 to 0.86) and to influenza-vaccinated patients was 0.88 (0.85 to 0.89). However, stroke incidence rates were lower in the herpes zoster-vaccinated group prevaccination compared with both comparator cohorts. The SCCS found no association between herpes zoster vaccination and stroke 30–119 days later.Conclusions Despite our cohort study, with extensive confounder adjustment and an influenza vaccination active comparator, finding herpes zoster vaccination associated with 12%–16% reduced stroke rates, additional analyses suggested this was largely explained by healthy vaccinee bias. Our study illustrates the importance of robust sensitivity analyses and testing the suitability of causal inference tools for observational vaccine studies.